Does the EU need a new common migration policy? Evidence-based insights from Germany and Greece - Eugenia Vella (EconPol Forum, 2025)
Migration can stimulate economic growth when managed strategically. Heterogeneous impacts require targeted and redistributive policies. Narratives of migration as purely a supply-side issue are overly reductive. Migration can serve as a deficit-financing alternative to tax hikes or spending cuts. Achieving a new common migration policy may be more realistic through incremental steps.
Keywords: 330